Synthesis method and application of peroxymonosulfate activated catalyst
By synthesizing CoFe LDO/g-C3N4 composite materials, the PMS activation performance is improved, and the problem of low degradation efficiency and circulationability of organic pollutants such as acetaminophen in the prior art is solved, and rapid degradation and high stability are achieved.
Patent Information
- Application Number
- CN202411539411.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to efficiently degrade organic pollutants such as acetaminophen present in water, especially when treating wastewater containing large amounts of fluorine ions or multiple organic pollutants, the degradation efficiency and circulationability are not high.
By synthesizing CoFe LDO/g-C3N4 composite materials, the performance and recyclability of permonosulfate (PMS) activation are improved, so that it has excellent activation properties in PMS, thereby achieving rapid degradation of organic pollutants such as acetaminophen.
The rapid degradation of organic pollutants such as acetaminophen has been achieved, the efficiency of environmental pollution control has been improved, the catalyst has high stability and reusability, and the frequency and cost of catalyst replacement have been reduced.
Smart Images

Figure CN119746901A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts and wastewater treatment, and in particular to a method for degrading organic pollutants such as acetaminophen by using an efficient and stable PMS activated catalyst. Background Art
[0002] In recent years, paracetamol is one of the most effective analgesics and has been widely used to relieve mild and moderate pain. Due to its physicochemical properties, paracetamol and other emerging pollutants of concern are difficult to degrade below a lower concentration range by conventional methods or some high-efficiency technologies such as reverse osmosis, making this drug a persistent pollutant in water. Traditionally, advanced oxidation processes based on the generation of hydroxyl radicals are considered to be an effective method for destroying recalcitrant organic matter in water. However, advanced oxidation processes based on sulfate radicals have attracted increasing attention due to their higher oxidation potential, wider working pH range and longer half-life. Therefore, the treatment of these pollutants in water bodies has become an environmental issue that needs to be urgently addressed.
[0003] Layered double hydroxides (LDHs), also known as hydrotalcite-like compounds, are a class of ionic layered compounds consisting of positively charged brucite-like layers and charge-compensating anion interlayers, which have large surface areas, high structural stability, and excellent metal oxide dispersibility. However, the efficiency of AOPs is limited by the reduced number of PMS activation sites occupied by short-lived free radicals (half-life of 30-40 μs for sulfate radicals and less than 1 μs for hydroxyl radicals) and inactive cations such as Mg and Al. In order to make free radicals and organic pollutants more accessible, it is highly desirable to construct catalysts with both adsorptive and catalytic activities. The six nitrogen lone pairs in g-C3N4 act as electron donors, thereby providing sites for transition metal ions. In addition, the abundant pyrrolidino nitrogen in g-C3N4 provides adsorption sites for organic pollutants. The understanding of the role and synergistic effects of g-C3N4 remains unexplained. A method for improving the performance and recyclability of peroxymonosulfate (PMS) activation by synthesizing CoFe LDO / g-C3N4 composite materials, so that it has excellent activation performance in PMS, thereby achieving rapid degradation of organic pollutants such as acetaminophen. For example, a Chinese patent with publication number CN116573746A discloses a method for improving the peroxymonosulfate activation efficiency by adding fluoride ions and interacting with a catalyst. The method is simple to operate and has a wide range of applications, and is particularly suitable for treating wastewater containing fluoride ions. However, if a large amount of wastewater containing fluoride ions needs to be treated, or a variety of organic pollutants need to be treated, the degradation efficiency and recyclability are not high. Therefore, how to obtain a method that can improve the performance of peroxymonosulfate activation and improve its recyclability, and effectively degrade pollutants, is urgently needed. Summary of the invention
[0004] In scientific research or technological development, the specific goals to be achieved and the problems to be solved through experiments. The object of the present invention is to develop an efficient catalyst for activating peroxymonosulfate (PMS) to degrade organic pollutants, especially acetaminophen.
[0005] Another object of the present invention is to explore the effects of different synthesis conditions on catalyst performance in order to optimize the activity, stability and reusability of the catalyst.
[0006] Another object of the present invention is to study the mechanism of catalyst activation of PMS, including the generation of free radicals, the electron transfer process and the interaction between the catalyst and the pollutant.
[0007] In order to achieve the above object, the present invention is implemented by the following technical solutions:
[0008] A method for synthesizing a peroxymonosulfate activated catalyst and its application, wherein the preparation process of the catalyst comprises the following steps:
[0009] (1) Co(NO3)2·6H2O and Fe(NO3)3·9H2O were mixed and dissolved in deionized water to form a mixed solution.
[0010] (2) The mixed solution was slowly added dropwise to an alkaline medium (2 M NaOH and 1 M Na2CO3) and the pH value was adjusted to 10.
[0011] (3) The formed suspension was aged, filtered under vacuum, washed with ethanol, and dried to obtain CoFeLDH.
[0012] (4) Four different amounts of CoFe LDH were mixed with melamine, added into deionized water and stirred continuously until all the water evaporated.
[0013] (5) The obtained solid product is calcined to polymerize melamine and oxidize CoFe LDH, and finally a CoFe LDO / g-C3N4 composite material is obtained. The obtained product is washed with deionized water and ethanol for several times.
[0014] (6) Batch experiments were conducted in a 250 mL beaker containing 100 mL of 10 mg / L paracetamol solution at 25 ± 0.5 °C and a stirring speed of 300 rpm.
[0015] (7) Add the required amount of PMS and catalyst to the target pollutant solution. Take 1 mL of the solution sample regularly at given time intervals and filter it through a 0.45 μm filter pore.
[0016] (8) The sample was mixed with 0.5 mL of MeOH to quench the degradation reaction, and the residual paracetamol concentration was determined by high performance liquid chromatography (HPLC).
[0017] (9) The solution after the experiment was filtered through a 0.45 μm cellulose filter, washed and dried at 80°C overnight for the next cycle.
[0018] (10) The prepared catalysts were systematically characterized, and their degradation performance was evaluated under different experimental conditions.
[0019] In the above technical scheme, all the measurements are repeated and the average value is used. The error bar represents the standard deviation. The corresponding reaction rate constant adopts the pseudo first-order rate equation ln(C / C0)=-k obs t calculation.
[0020] In the above technical solution, in step (10), the degradation efficiency of paracetamol by g-C3N4 alone is relatively weak, indicating that g-C3N4 cannot effectively activate PMS. The removal of paracetamol by the g-C3N4-PMS system mainly occurs in the first 10 minutes. This should be attributed to the appropriate adsorption capacity of g-C3N4, and the system reaches adsorption equilibrium within 10 minutes. When the CoFe LDO / g-C3N4 content is 0.6, the removal rate of the composite material increases with the increase of CoFe LDO content, and its kinetic constant k obs 0.386min -1 ; When the CoFeLDO content increases, the removal rate decreases.
[0021] In the above technical scheme, the catalyst (0.2 g / L) can degrade 10 mg / L of paracetamol in less than 10 min using 0.5 mM PMS concentration at neutral pH. Using the same model molecule as the pollutant for comparison, few catalysts can achieve complete removal of paracetamol within 10 min. We found that the Mn2O3 / Fe2O3 composite material can degrade 15 mg / L paracetamol within 10 min, but the high leaching of Mn-metal and acidic medium reduce the stability of the composite material. CoFeO2 / g-C3N4 was used to remove levofloxacin as the target pollutant, but 100% removal rate was achieved within 60 min. This clearly shows that the CoFe LDO / g-C3N4 system has superior performance.
[0022] In the above technical scheme, the effect of different synthesis conditions on the performance of the catalyst is explored to optimize the activity, stability and reusability of the catalyst. The CoFe LDO / g-C3N4 composite material is prepared by coprecipitation and hydrothermal method. The catalyst is characterized by means of XRD, TGA, HRTEM, SEM, BET, XPS and XAS. The effect of the catalyst on the PMS activation and degradation of acetaminophen is studied by degradation experiments. The PMS activation mechanism of the catalyst is studied by ESR, XPS, XAS and electrochemical experiments.
[0023] In the above technical solution, the persulfate is peroxymonosulfate.
[0024] Compared with the prior art, the technical solution of the present invention produces the following beneficial technical effects:
[0025] 1. The developed catalyst can efficiently activate PMS and achieve rapid degradation of organic pollutants such as acetaminophen, thereby improving the efficiency of environmental pollution control. The optimized catalyst has high stability and can maintain high catalytic activity after multiple cycles, reducing the frequency and cost of catalyst replacement.
[0026] 2. Through in-depth research on the mechanism of catalyst activation of PMS, we can better understand the chemical process of organic pollutant degradation and provide a theoretical basis for designing more effective catalysts. Evaluating the effect of catalysts under different water quality conditions will help determine their application potential in actual environmental governance and provide a scientific basis for promotion and application. Developing environmentally friendly treatment technologies will help reduce the use of chemical substances, reduce environmental pollution, and promote environmental protection and sustainable development.
[0027] 3. The present invention prepares CoFe LDO / g-C3N4 catalyst, which can degrade acetaminophen in PMS activation, quickly degrade organic pollutants, improve treatment efficiency, and reduce treatment time. The synthesis and application process of the catalyst is relatively environmentally friendly, reducing the impact on the environment. It has good stability and reusability, reduces operating costs and resource consumption, and the optimized reaction conditions are simple and easy to operate, and are easy to apply in actual environments. The cost of the catalyst is relatively low, and it can save resources and improve economic benefits in long-term use, providing a new solution for environmental purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The proposed PMS activation mechanism by CoFe LDO / g-C3N4 composites;
[0029] Figure 2(a) low-magnification TEM micrograph of 0.6CoFeLDO / g-C3N4, (b) HRTEM micrograph of 0.6CoFe LDO / g-C3N4 (the inset shows the detailed area of anchored CoFe LDO), (c) STEM image of 0.6CoFeLDO / g-C3N4 and (d) the corresponding STEM-haadf micrograph;
[0030] Figure 3 Removal rate of acetaminophen × CoFe LDO / g-C3N4 (x = 0, 0.2, 0.4, 0.6 and 0.8) (a) and the corresponding reaction rate constant (b);
[0031] Figure 4 This is the effect of different catalyst dosages on the catalytic degradation of acetaminophen;
[0032] Figure 5 This is the effect of different doses of PMS on the catalytic degradation of acetaminophen;
[0033] Figure 6 This is the effect of different initial pH values on the catalytic degradation of acetaminophen;
[0034] Figure 7 The effect of the coexistence of anions on the catalytic degradation of acetaminophen is shown in the figure;
[0035] Figure 8 (a) XRD spectra of original and recycled 0.6CoFe LDO / g-C3N4, (b) effect of experimental cycle on acetaminophen removal rate, (c) Co and Fe leaching diagrams of CoFe LDO and CoFe LDO / g-C3N4 at different initial pH;
[0036] Fig. 9 This is a graph showing the effect of different free radical scavengers on the removal of paracetamol;
[0037] Fig.10 This is a PMS decomposition diagram;
[0038] Fig.11 ESR spectra of 20 mM DMPO (upper) and 20 mM TEMP (lower) as spin trapping agents;
[0039] Fig.12 is the time current curve;
[0040] Fig.13 It is the LSV curve diagram;
[0041] Fig.14 It is the CV curve diagram;
[0042] Fig.15 Normalized XANES spectra of Co k-edge of standard compound (dashed line) and sample (solid line);
[0043] Fig.16 Normalized XANES spectra of Fe k-edge of standard compound (dashed line) and sample (solid line). DETAILED DESCRIPTION
[0044] The following examples further illustrate the method for improving the performance and recyclability of peroxymonosulfate activation according to the present invention. It is necessary to point out that the following examples are only used to further illustrate the present invention.
[0045] Embodiment 1:
[0046] In this embodiment, a synthesis method and application of a peroxymonosulfate activated catalyst according to the present invention are provided, and the steps are as follows:
[0047] (1) Co(NO3)2·6H2O and Fe(NO3)3·9H2O were mixed and dissolved in deionized water to form a mixed solution.
[0048] (2) The mixed solution was slowly added dropwise to an alkaline medium (2 M NaOH and 1 M Na2CO3) and the pH value was adjusted to 10.
[0049] (3) The formed suspension was aged, filtered under vacuum, washed with ethanol, and dried to obtain CoFeLDH.
[0050] (4) Four different amounts of CoFe LDH were mixed with melamine, added into deionized water and stirred continuously until all the water evaporated.
[0051] (5) The obtained solid product is calcined to polymerize melamine and oxidize CoFe LDH, and finally a CoFe LDO / g-C3N4 composite material is obtained. The obtained product is washed with deionized water and ethanol for several times.
[0052] (6) Batch experiments were performed in a 250 mL beaker containing 100 mL of a 10 mg / L paracetamol solution at 25 ± 0.5 °C and a stirring speed of 300 rpm.
[0053] (7) Add the required amount of PMS and catalyst to the target pollutant solution. Take 1 mL of the solution sample regularly at given time intervals and filter it through a 0.45 μm filter pore.
[0054] (8) The sample was mixed with 0.5 mL of MeOH to quench the degradation reaction, and the residual paracetamol concentration was determined by high performance liquid chromatography (HPLC).
[0055] (9) The solution after the experiment was filtered through a 0.45 μm cellulose filter, washed and dried at 80°C overnight for the next cycle.
[0056] (10) The prepared catalysts were systematically characterized, and their degradation performance was evaluated under different experimental conditions.
[0057] Through the characterization and analysis of the CoFe LDO / g-C3N4 catalyst, Fe and Co foil were used as energy calibration, and FeO, Fe3O4, Fe2O3, CoO, Co3O4 and LaCoO3 standards were measured under the same sample conditions and used as reference compounds for the determination of Fe and Co k-edge valence states. It was further revealed that the valence states of Co and Fe in the catalyst were low, which was conducive to the activation of PMS; x-ray photoelectron spectroscopy (XPS) was performed on a PHI VersaProbe II instrument equipped with a monochromatic Al kα source. The XPS data were charge corrected, and the binding energy of carbon 1s foreign hydrocarbons was obtained to be 284.8 eV, with Ag / AgCl as the reference electrode. 7μL of ink catalyst prepared by thoroughly mixing 10mg of catalyst with 10mg of conductive carbon, 1mL of anhydrous ethanol and 0.1mL of perfluorosulfonic acid solution (5wt%) was dropped on a glassy carbon rod with a diameter of 4mm to prepare a working electrode. The stoichiometric value of CoFe LDO is Co 2.25 Fe 0.75O4 In the spinel-like structure, the ratio of Co and Fe is 3:1. Since the graphite-like g-C3N4 structure has a strong preferential orientation along the (002) plane, its diffraction maximum contributes more strongly to the entire diffraction pattern, making the XRD spectrum of the CoFe LDO compound difficult to observe. However, the presence of CoFe LDO compounds in the composite material has been confirmed by other complementary techniques (TEM, scanning electron microscopy and EXAFS). In order to further confirm its composition and thermal stability, TGA analysis was performed using ×CoFe LDO / g-C3N4 (x=0.2, 0.4, 0.6 and 0.8). TGA characterization showed that the catalyst has high thermal stability. Corresponding to CoFe LDO / g-C3N4, CoFe LDO is correctly anchored on the surface of g-C3N4 nanosheets, thereby achieving covalent interfacial interactions. The catalyst has uniform nanoscale particles and surface morphology such as Figure 2 As shown. BET characterization shows that the catalyst has a large specific surface area, which is conducive to the exposure of active sites. It has high electrochemical activity. It can also generate various types of free radicals, which is conducive to the degradation of organic pollutants.
[0058] In addition, the catalytic performance analysis showed that the degradation efficiency of paracetamol by g-C3N4 alone was weak, indicating that g-C3N4 could not effectively activate PMS. The removal of paracetamol by the g-C3N4-PMS system mainly occurred in the first 10 minutes, which should be attributed to the appropriate adsorption capacity of g-C3N4. The system reached adsorption equilibrium within 10 minutes. When the CoFe LDO / g-C3N4 content was 0.6, the removal rate of the composite material increased with the increase of CoFe LDO content, and its kinetic constant k obs 0.386min -1 ; When the CoFe LDO content increases, the removal rate decreases. Figure 3 As shown, the catalytic performance of different LDO contents is in the order of 0.6>0.4>0.8>0.2CoFe LDO / g-C3N4. This order is related to the BET surface area results, highlighting the importance of the specific area of PMS activation and the number of active sites. The performance of the CoFe LDO / PMS system was tested, and the results showed that the difference of CoFe LDO / g-C3N4 was 0.8. The adsorption capacity of 0.6CoFe LDO / g-C3N4 for paracetamol was studied by measuring the pollutant concentration after 30 minutes. The initial concentration of paracetamol was reduced by 6.8%, indicating that the adsorption of paracetamol was not significant, and the removal of paracetamol was mainly a degradation process. With 0.6CoFe LDO / g-C3N4 as the catalyst, TOC decreased by 53% after 60 minutes of reaction, indicating that the mineralization degree of acetaminophen was significant. Therefore, 0.6CoFe LDO / g-C3N4 is the best ratio. The catalyst (0.2 g / L) can degrade 10 mg / L of paracetamol in less than 10 min using 0.5 mM PMS concentration at neutral pH. Using the same model molecule as the pollutant for comparison, few catalysts can achieve complete removal of paracetamol within 10 min. CoFeO2 / g-C3N4 was used to remove levofloxacin as the target pollutant, but 100% removal was achieved within 60 min. This clearly shows the superior performance of the CoFe LDO / g-C3N4 system.
[0059] Embodiment 2:
[0060] This example is based on the above examples to analyze the catalytic degradation of acetaminophen under different conditions. Figure 4-7 shown.
[0061] Figure 4 The figure shows the effect of different catalyst dosages on the catalytic degradation of acetaminophen. Figure 4It can be seen that changing the dosage of CoFe LDO / g-C3N4 has a great influence on the decomposition efficiency of paracetamol. When the catalyst dosage is 0.05g / L and PMS is 0.5mM, the removal efficiency of paracetamol is 95% in 60min. Under the same PMS dosage and pollutant concentration, when the catalyst dosage is 0.2g / L, the removal efficiency of paracetamol is 98% in 10min. As the catalyst dosage increases from 0.073 to 0.386min -1 This observation is consistent with the fact that increasing the amount of catalyst may provide more active sites for PMS activation and the reaction rate is limited by the number of active sites.
[0062] Figure 5 The figure shows the effect of different doses of PMS on the catalytic degradation of acetaminophen. Figure 5 It can be seen that when the dosage of acetaminophen is 10 mg / L and the dosage of catalyst is 0.2 g / L, different PMS dosages affect its degradation. Increasing the dosage of PMS can improve the degradation efficiency of acetaminophen. When the PMS addition reaches 0.5 mM, more than 97% of acetaminophen can be removed within 10 minutes. However, when the PMS addition amount is continuously increased to 1 mM, due to the excessive PMS, the available active sites are limited and the catalytic oxidation performance cannot be further significantly improved. On the other hand, higher doses of PMS may limit the efficiency of the sulfate radical process.
[0063] Figure 6 The figure shows the effect of different initial pH values on the catalytic degradation of acetaminophen. Figure 6 It can be seen that the removal efficiency of acetaminophen slightly increased when the initial pH increased from 3 to 7, while the degradation performance decreased when the pH increased to 9. Considering the different forms of PMS present in the pH range studied, the trend observed during the degradation process is that at very low pH values (pKa1 < 0), H2SO5 is the most stable form of PMS, which limits the generation of ROS. Under moderately acidic and neutral conditions, HSO5 - obtain activity, allowing optimal ROS generation, but when the pH exceeds 9.4 (pKa2 = 9.4), SO5 2— It is the main anion, and HSO5 - In contrast, it has shown disappearance characteristics in PMS activation. - Will clear According to Equation 1, ·OH radicals are the only oxidants present in strongly alkaline solutions, and according to Equation 2, sulfate radicals can also be quenched by water molecules, leading to low organic decomposition.
[0064]
[0065] Figure 7 The figure shows the effect of the coexistence of anions on the catalytic degradation of acetaminophen. Figure 7 It can be seen that in the presence of anions, the degradation rate Cl - <HCO3 - <NO3 - As mentioned above, Cl - Can react with HSO5 - The reaction generates HClO and Cl2, as shown in Equation 3-5, which is considered to be a weaker ROS than PMS. - Also OH and Scavenger (free radicals with lower redox potential CO3 ·- ) as in formula 6-7. NO3 was not observed - The obvious effect of Figure 7 The changes in the kinetic degradation constants are clearly shown in Fig.
[0066] Cl - +HSO3 - →SO4 2- +HClO Formula-3
[0067] 2Cl - +HSO5 - +H + →SO4 2- +Cl2+H2O Formula-4
[0068]
[0069] HCO3 - + ·OH→H2O+CO3 ·- Formula-7
[0070] Embodiment 3:
[0071] Based on the above examples, this example conducted a recycling example to evaluate the recyclability of CoFe LDO / g-C3N4 and CoFeLDO. Figure 8 (a) shows that the crystal structure remains stable after continuous degradation cycles. Figure 8 As shown in (b), with CoFe LDO / g-C3N4 as the catalyst, the removal rate of paracetamol reached more than 95% within 30 min of the fourth run. On the other hand, from the perspective of continuous removal cycles, the reusability of CoFe LDO is not as good as that of CoFe LDO / g-C3N4, and the incomplete removal of paracetamol is particularly obvious after the fourth run. The leaching concentrations of Co and Fe at different pH values were further determined. Figure 8As shown in (c), the metal leaching rate of CoFe LDO / g-C3N4 is much lower than that of CoFe LDO in the entire pH range studied (pH 3 to 9).
[0072] Embodiment 4:
[0073] In order to determine the main ROS in the degradation of acetaminophen, this example uses a chemical probe method with MeOH, TBA and FFA as scavengers. Methanol is an alpha-hydrogen-containing alcohol that can react with SO4 at a similar high rate. ·- In this example, two free radical scavengers were used. MeOH and TBA were used to quench and OH. Fig. 9 As shown in Figure 2, when 100 mM and 500 mM MeOH were added, the removal rates of acetaminophen within 60 min were 53.3% and 48.8%, respectively. This indicates that ·OH is not the main ROS, based on the capture of ·OH radicals by TBA. Fig.10 As shown in Figure 2, FFA did not significantly promote the decomposition of PMS in the presence or absence of a catalyst. Therefore, the inhibition of paracetamol degradation by FFA is likely due to the interaction of FFA with 1 Direct reaction of O2, rather than decomposition of PMS.
[0074] Embodiment 5:
[0075] Based on the above examples, the following examples were conducted to confirm the preliminary conclusions obtained by the chemical probe method. We conducted further ESR measurements. Fig.11 As shown in the figure, when DMPO was added as a spin trapping agent, no characteristic signal was observed for PMS alone. However, in the presence of PMS and catalyst CoFe LDO / g-C3N4, the characteristic signals of DMPOX adduct (1:2:1:2:1:1) appeared simultaneously, which may be due to the direct oxidation of DMOP or the peroxidation of DMPO-SO4 or DMPO-OH adducts by PMS through the ROS generated after catalyst activation. It is worth mentioning that even in the 2min ESR spectrum, the DMPOX signal is dominant, indicating that the catalyst has a high PMS activation efficiency. Despite the ·OH, and 1 O2 free radicals exist, Free radicals play an important key role in the paracetamol removal process.
[0076] Embodiment 6:
[0077] This example further electrochemical experiments were performed based on the above examples to illustrate the electron transfer process. Chronoamperometric measurements were performed using a catalyst-modified glassy carbon electrode by tracking the current response of sequentially adding PMS and paracetamol. Fig.12 It can be seen that when the working electrode is g-C3N4 alone, the effect of adding the first PMS and the second paracetamol on the current is negligible, indicating that there is no electron transfer when neither PMS nor paracetamol is added. However, when the working electrode is composed of CoFe LDO, the current suddenly drops after the addition of PMS, indicating that the reduction of PMS is accompanied by the oxidation of transition metal active sites and the generation of oxidative free radicals, and there is an electron transfer process. The subsequent addition of paracetamol caused a further significant drop in the current, which was due to the transfer of electrons from paracetamol to PMS mediated by CoFe LDO. When paracetamol was added, there was a current response on the electrode material, which clearly indicated the existence of an electron transfer process, which also confirmed that paracetamol was degraded through the electron transfer pathway. As shown respectively Fig.13 and 14 As shown in Figure 2, the electron transfer kinetics and transport properties of the degradation reaction were studied. The current response of CoFe LDO / g-C3N4 changes with voltage ( Fig.13 ), CoFe LDO has a larger current density than g-C3N4, showing a stronger ability for redox processes and further conversion reactions. The peak observed in the current indicates the growth of a diffusion layer on the electrode surface, which makes the flux of reactants to the electrode not fast enough to satisfy the conversion at this potential. The current maximum occurs at similar voltages, indicating that CoFe LDO and CoFe LDO / g-C3N4 have similar electron transfer kinetics. Fig.14 A typical cyclic voltammogram is shown, showing a similar response to the LSV experiment.
[0078] Embodiment 7:
[0079] In this example, the electronic structure of transition metal cations was analyzed using XAS. After CoFe LDO was composited with g-C3N4, the oxidation state and coordination environment at the Co k-edge and Fe k-edge changed. Fig.15 The normalized X-ray absorption near-edge structure (XANES) of the sample measured at the Co k-edge is shown. The increase in the intensity of the front edge peak associated with the 1s and 3d transitions at about 7709.5 eV after recombination with g-C3N4 can be attributed to the higher inverse ratio. The XANES spectrum at the Fe k-edge (e.g. Fig.16 The peak shown in Figure 3 shows similar characteristics to the edge front peak.
[0080] Based on the analysis of the above examples, the PMS activation mechanism was proposed. 2+ and Fe2+ Activated HSO5 - generate ·OH can also be generated. This process is enhanced because the covalent effect of mixing the CoFe LDO composite with g-C3N4 reduces the valence of Co and Fe. Subsequently, the oxidized Co 3+ and Fe 3+ HSO5 - Reduction to Co 2+ and Fe 2+ (As shown in formula 8-9). 1 The O2 rule is negligible in the decomposition process but can be formed by the self-decomposition of PMS as shown in Eqs. 10 and 11. According to the reactions described in Eqs. 12 and 13, hydroxyl radicals (·OH) are also predicted due to the interaction of sulfate radicals with the aqueous medium. On the other hand, the electrons from the direct oxidation of paracetamol reduce Fe and Co, which are then oxidized by PMS, leaving the catalyst unchanged during the pure electron transfer degradation process. Then, two opposing degradation mechanisms operate in the catalyst. On the one hand, the low Co / Fe oxidation state will promote the generation of radicals through PMS activation, and on the other hand, the high Co / Fe valence state will promote faster electron transfer from paracetamol to the catalyst.
[0081]
[0082] ≡Co 3+ / Fe 3+ +HSO5 - →≡Co 2+ / Fe 2+ +SO5 ·- +H + Formula-9
[0083] HSO5 - →SO5 2- +H + Formula-10
[0084] SO5 2- +HSO5 - →HSO4 - +SO5 2- +O2 Formula-11
[0085]
[0086] Based on the above examples, we found that the effect of g-C3N4 on reducing the valence states of Co and Fe in CoFe LDO compounds stimulated PMS activation and concomitant paracetamol degradation. By combining ESR and XPS tests with XAS and electrochemical measurements, free radical mediation and electron transfer processes were considered to be two mechanisms for enhanced degradation. According to the changes in catalyst and PMS, detailed degradation conditions (0.2g / L CoFe LDO / gC3N4, 0.5mM PMS, pH=7) were obtained. It further revealed The important role of free radical and electron transfer processes, which synergistically promoted the degradation of acetaminophen in less than 10 min under dark conditions. In addition, recycling experiments and metal leaching tests verified the good reusability and stability of the catalyst. These findings open up a new approach for the mechanistic coupling of free radical and electron-electron transfer processes and may be of great significance for the development of wastewater treatment materials.
[0087] While embodiments of the present invention have been shown and described, it will be apparent to those skilled in the art that various changes, modifications, substitutions and alterations may be made to such embodiments without departing from the principles and objectives thereof, the scope of the invention being defined by the claims and their equivalents.
Claims
1. A method for synthesizing a peroxymonosulfate activated catalyst and its application, characterized in that: CoFe LDH was prepared by coprecipitation, and then mixed with melamine by hydrothermal method to form CoFeLDO / g-C3N4 composite material for catalyzing peroxymonosulfate (PMS). The performance and recyclability of PMS activation were improved by considering multiple factors, and a more efficient and stable PMS activation technology was developed through continuous exploration and innovation.
2. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The specific preparation process of the catalytic persulfate composite material includes the following steps: (1) Co(NO3)2·6H2O and Fe(NO3)3·9H2O were mixed and dissolved in deionized water to form a mixed solution. (2) The mixed solution was slowly added dropwise to an alkaline medium (2 M NaOH and 1 M Na2CO3) and the pH value was adjusted to 10. (3) The resulting suspension was aged, filtered under vacuum, washed with ethanol, and dried to obtain CoFe LDH. (4) Four different amounts of CoFe LDH were mixed with melamine, added into deionized water and stirred continuously until all the water evaporated. (5) The obtained solid product is calcined to polymerize melamine and oxidize CoFe LDH, and finally a CoFeLDO / g-C3N4 composite material is obtained. The obtained product is washed several times with deionized water and ethanol.
3. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The specific method for improving performance and recyclability includes the following steps: (1) Batch experiments were conducted in a 250 mL beaker containing 100 mL of a 10 mg / L paracetamol solution at 25 ± 0.5 °C and a stirring speed of 300 rpm. (2) Add the required amount of PMS and catalyst to the target pollutant solution. Take 1 mL of the solution sample regularly at given time intervals and filter it through a 0.45 μm filter pore. (3) The sample was mixed with 0.5 mL of MeOH to quench the degradation reaction, and the residual paracetamol concentration was determined by high performance liquid chromatography (HPLC). (4) The solution after the experiment was filtered through a 0.45 μm cellulose filter, washed and dried at 80°C overnight for the next cycle. (5) The prepared catalyst was systematically characterized, and its degradation performance was evaluated under different experimental conditions.
4. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 2, characterized in that: In step (3), the aging temperature is 60°C and the time is 24 hours. The product is washed with ethanol and dried at 80°C for 24 hours to obtain CoFe LDH.
5. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 2, characterized in that: In step (4), the stirring temperature is 80° C., and the stirring process is completed by magnetic stirring using a magnetic stirrer.
6. A method for improving the performance and recyclability of peroxymonosulfate activation according to claim 2, characterized in that: In step (5), the calcination reaction temperature is 550° C. and the calcination time is 2.5 h.
7. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 3, characterized in that: In step (3), the paracetamol concentration is determined by HPLC, the chromatographic column is Jasco MD-2010 / 2015, the chromatographic column is 5μmC18 (4.6mm×250mm), and the UV / visible detector is used.
8. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The optimization experiment was carried out to select the appropriate PMS concentration to avoid excess or deficiency of PMS. Excess PMS may lead to the deactivation of the catalyst, while deficiency of PMS may lead to a decrease in the reaction rate.
9. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The optimization experiment was carried out to select the appropriate amount of catalyst to avoid excessive or insufficient catalyst. Excessive catalyst may lead to the formation of reaction by-products, while insufficient catalyst may lead to a decrease in reaction rate.
10. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The optimization experiment was carried out to select a suitable pH value to improve the activation of PMS and the generation efficiency of ROS. The pH value will affect the dissociation degree of PMS and the stability of ROS.
11. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The optimization experiment was carried out to select the appropriate temperature to improve the reaction rate and efficiency. Too high a temperature may lead to the deactivation of the catalyst, while too low a temperature may lead to a decrease in the reaction rate.
12. The method for synthesizing a peroxymonosulfate activated catalyst and its application according to claim 1, characterized in that: The optimization experiment was carried out to select a suitable stirring rate to improve the mass transfer efficiency between the reactants. Too high a stirring rate may cause the catalyst to wear, while too low a stirring rate will reduce the mass transfer efficiency between the reactants.
Citation Information
Patent Citations
Method for improving persulfate activation efficiency of catalyst
CN116573746A
Cited By
Preparation method of cobalt modified polyheptazinyl imide and application of cobalt modified polyheptazinyl imide in rhodamine B photosensitization detection of paracetamol
CN120665286A